تنمية المحتوى الوطني (المحلي) في صناعة النفط والغاز وآليات تحسين الأداء - اسماعيل , هلال علي (Journal of Petroleum Research and Studies, 2019)
Adequate balance between the requirements of local content supporting of development of investment is highly complicated of critical process, which need a comprehensive vision of all surrounding circumstances. Dealing mechanisms varied depending upon the nature and size of project or investment opportunity. The endeavors for obtaining high level of local content will and reflected in national economy and more value added in it due to the direct, indirect and induced impact in other sectors, this research aim to find the best practices in local content and adopt the mesures to be applied.